2021
DOI: 10.2196/27848
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Physical-Cognitive Game-Based Training System Using Kinect for Older Adults: Development and Usability Study

Abstract: Background Declines in physical and cognitive functions are recognized as important risk factors for falls in older adults. Promising evidence suggests that interactive game-based systems that allow simultaneous physical and cognitive exercise are a potential approach to enhance exercise adherence and reduce fall risk in older adults. However, a limited number of studies have reported the development of a combined physical-cognitive game-based training system for fall risk reduction in older adults… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 76 publications
2
7
0
Order By: Relevance
“…Moreover, age showed no relationship with the dimensions and total score of the scales when evaluated. Finally, the ceiling effect observed in questionnaire responses has also been highlighted in previous studies, such as that of Kamnardsiri et al [ 43 ], in assessing the enjoyment of an interactive game in older adults. Likewise, Ryuh et al [ 44 ] observed this effect when promoting PA through exergaming in people with intellectual disabilities.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, age showed no relationship with the dimensions and total score of the scales when evaluated. Finally, the ceiling effect observed in questionnaire responses has also been highlighted in previous studies, such as that of Kamnardsiri et al [ 43 ], in assessing the enjoyment of an interactive game in older adults. Likewise, Ryuh et al [ 44 ] observed this effect when promoting PA through exergaming in people with intellectual disabilities.…”
Section: Discussionsupporting
confidence: 59%
“…This literature review showed that positive effects were found in the elderly who underwent the computer/mobile phone‐based brain training game program. Some studies reported benefits not just in the psychological dimension, but also in the physical dimension 22 . The variation in the studies depended on the type of brain training game provided, the measurement tools used, and the baseline brain competency (the level of decline in brain memory function) of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported benefits not just in the psychological dimension, but also in the physical dimension. 22 The variation in the studies depended on the type of brain training game provided, the measurement tools used, and the baseline brain competency (the level of decline in brain memory function) of the subjects. The setting that had more facility, expertise healthcare workers can be use more sensitive tools such as neurological test equipment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the importance of technology in fall rehabilitation and prevention has been increasingly studied, even in older individuals. This is relevant because, in recent years, great importance has been given to interactive technological physical and physical-cognitive training programs, which have proven effective in reducing the risk of falls [90][91][92]. With technology, it is possible to make precise measurements of certain parameters that are expressions of complex functions, such as balance.…”
Section: Technologymentioning
confidence: 99%